Colonoscopy and Flexible Sigmoidoscopy Practice Patterns in Ontario: A Population-Based Study - Susan E Schultz; Chris Vinden; Linda Rabeneck (Canadian Journal of Gastroenterology)
OBJECTIVE: To conduct a population-based study on the provision of large bowel endoscopic services in Ontario.